2005
DOI: 10.1177/0148607105029006445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parenteral Nutrition on Nutrition Status After Bariatric Surgery for Morbid Obesity

Abstract: (1) Nutrition status after BS PO and 30 days postsurgery was no different between PN and nPN. (2) Postsurgery hospital stay was significantly decreased in the nPN group, without a greater incidence of complications. (3) According to nutrition outcome, PN seems unnecessary at the perioperative period in BS unless there are other postsurgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Anastomotic leaks and SBO may be treated operatively or nonoperatively and may also necessitate a prolonged course of NPO (nil per os) with parenteral nutrition (PN) support until resolution of the complication 6 9 . Studies have reported the use of PN in the hospitalized patient following bariatric surgery complications, but none have been reported on the use of long‐term or home PN (HPN) in this patient population 10 12 . The aim of our study was to determine if hypocaloric HPN provided to obese patients for complications following bariatric surgery had an effect on BMI, serum albumin level, and HPN complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastomotic leaks and SBO may be treated operatively or nonoperatively and may also necessitate a prolonged course of NPO (nil per os) with parenteral nutrition (PN) support until resolution of the complication 6 9 . Studies have reported the use of PN in the hospitalized patient following bariatric surgery complications, but none have been reported on the use of long‐term or home PN (HPN) in this patient population 10 12 . The aim of our study was to determine if hypocaloric HPN provided to obese patients for complications following bariatric surgery had an effect on BMI, serum albumin level, and HPN complications.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] Studies have reported the use of PN in the hospitalized patient following bariatric surgery complications, but none have been reported on the use of long-term or home PN (HPN) in this patient population. [10][11][12] The aim of our study was to determine if hypocaloric HPN provided to obese patients for complications following bariatric surgery had an effect on BMI, serum albumin level, and HPN complications.…”
mentioning
confidence: 99%
“…The Allied Health Nutritional Guidelines for the Surgical Weight Loss Patient do not recommend PN on a regular basis [442]. In these patients the GI tract is usually working and catheter associated complications have to be considered [450].…”
Section: Commentarymentioning
confidence: 99%
“…The Allied Health Nutritional Guidelines for the Surgical Weight Loss Patient do not recommend PN regularly [247]. In these patients, the gastrointestinal tract is usually working and catheter-associated complications have to be considered [255].…”
Section: Recommendation 34mentioning
confidence: 99%